2018
DOI: 10.1093/eurheartj/ehx760
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability and risk of cardiovascular events and death in patients with hypertension and different baseline risks

Abstract: Higher visit-to-visit systolic blood pressure variability is associated with increased risk of cardiovascular events in patients with hypertension, irrespective of baseline risk of cardiovascular events. Associations were stronger in younger patients and in those with lower mean systolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 31 publications
(23 reference statements)
10
136
1
3
Order By: Relevance
“…Meanwhile, as median layer calcification can decrease aortic compliance, making BP more likely to be affected by factors such as fluid load, posture and cardiac output change, it may increase mid‐term BPV. As BPV has been suggested to be a risk factor of cardiovascular events and mortality, it may contribute to the high mortality in CKD patients with VC.…”
Section: Disccusionmentioning
confidence: 99%
“…Meanwhile, as median layer calcification can decrease aortic compliance, making BP more likely to be affected by factors such as fluid load, posture and cardiac output change, it may increase mid‐term BPV. As BPV has been suggested to be a risk factor of cardiovascular events and mortality, it may contribute to the high mortality in CKD patients with VC.…”
Section: Disccusionmentioning
confidence: 99%
“…But there is no consensus yet on the relationship between BP, BPV, and cardiovascular risk. Mehlum et al [6] noticed that in patients with lower mean systolic BP, the association between BPV and cardiovascular events were stronger, while in several other studies, BPV was found to predict cardiovascular mortality independent of BP [5,7].…”
Section: Introductionmentioning
confidence: 97%
“…Although the treatment guidelines focus on average BP, evidences favoring BPV as the preferred metric are increasingly reported [5][6][7]. But there is no consensus yet on the relationship between BP, BPV, and cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for treatment of arterial hypertension recommend the assessment of the mean of office BP readings over several visits as the preferential method to assess the risk of cardiovascular events attributable to BP values and the need for antihypertensive therapy . However, several studies conducted on the general population have documented a relationship between increased long‐term blood pressure variability (BPV) and cardiovascular events and death, independently of mean BP . Similarly, high short‐term variability has been related to an increased cardiovascular risk by observational studies, although the level of evidence on the topic is still limited …”
Section: Introductionmentioning
confidence: 99%